Bare Below the Elbows: A Randomized Trial to Determine Whether Wearing Short-Sleeved Coats Reduces the Risk for Pathogen Transmission. (4th October 2017) - John, Amrita; Alhmidi, Heba; Gonzalez-Orta, Melany; Cadnum, Jennifer; Donskey, Curtis J
Abstract: Background: Physician's white coats are frequently contaminated, but seldom cleaned. Therefore, in the UK, a "bare below the elbows" dress code policy includes a recommendation that personnel wear short sleeves. However, it has not been demonstrated that wearing short sleeves reduces the likelihood of pathogen transmission. Methods: We conducted a randomized, cross-over trial involving simulated patient care interactions to test the hypothesis that transmission of pathogens occurs less frequently when personnel wear short- vs long-sleeved coats. Healthcare personnel were randomized to wear either long- or short-sleeved white coats while examining a mannequin contaminated with cauliflower mosaic virus DNA followed by examination of an uncontaminated mannequin. We compared the frequency of transfer of the DNA marker with the sleeves and/or wrists and with the uncontaminated mannequin. During work rounds, physicians were observed to determine how often the sleeves of white coats contacted patients or the environment. Results: During work rounds and simulated examinations, the sleeve cuff of long-sleeved coats frequently contacted the patient/mannequin or environment. Contamination with the DNA marker was detected significantly more often on the sleeves and/or wrists when personnel wore long- vs short-sleeved coats (5 of 20, 25% vs 0 of 20, 0%; P = 0.02). In one of five (20%) instances of sleeve and/or wrist contamination, the DNA marker was transferred to the second mannequin. It was also observed that healthcare personnel were less likely to include their wrist in handwashing between simulations if they were wearing long-sleeved coats. Conclusion: During simulations of patient care, the sleeve cuff of long-sleeved white coats frequently became contaminated with a viral DNA marker that could be transferred. These results provide support for the recommendation that healthcare personnel wear short sleeves to reduce the risk for pathogen transmission. Disclosures: All authors: No reported disclosures.